Efficacy and Safety of Bisphosphonate Therapy in Patients with Osteogenesis Imperfecta (Journal of Pakistan Orthopaedic Association, 2023)
Objective: To determine the efficacy and safety of bisphosphonate therapy in patients with osteogenesis imperfecta.Methods: 36 patients were included in this study, were of either gender with osteogenesis imperfecta (OI type I, II, III & IV). Patients with hypersensitivity to bisphosphonates, with extra-skeletal complications like pulmonary complications and poor tolerability to bisphosphonates were excluded. Informed written consent was taken. Patients were treated as outpatients on day care basis. Patients were subjected to intravenous BPs (alendronate) weight-dependent (0.5 mg-0.1mg/kg) per dose every 12 weeks. Patients were called for a follow up visit at 3rd and 6th month. The clinical evaluation of efficacy and safety was determined in terms of no fracture and no side effects respectively. Findings were recorded on a predesigned proforma and analyzed using SPSS v23.0. This was a descriptive case series study, conducted at the department of orthopedic surgery from Dec 2022 to May 2023.Results: The mean alkaline phosphate levels were 470.81+465.09 SD prior to BPs therapy and decreased to 226.92+79.35 SD after three months of BPs therapy. The comparison of means before and after BPs therapy showed significant results (p 0.003). Three months following BPs therapy, 17 (56.7%) males and 13 (43.3%) females had effective results (p 0.764) whereas BPs therapy was safe in 20 (57.1%) males and 15 (42.9%) females and only 01 (100.0%) patient showed mild symptoms of abdominal pain (p 0.257).Conclusion: Bisphosphonates therapy in children with osteogenesis imperfecta (OI) was effective and safe with a significant reduction in alkaline phosphate levels and decrease in the number of fractures post BPs therapy.